A Survey on Techniques of Critical Infrastructure Monitoring (International Journal of Engineering and Computer Science, 2018)
In our day today life electricity may be broken due to afternoon storms, snow storms and natural troubles. When these events occur we may think that it is due to some technical fault & the power will come after some time. If it is not coming, then we are calling to operator. Then the available artifacts and analytic techniques are applied to find the fault, determine the faulted area, complete repairs of that area and restoring service to that area. This is done by the control room staff by coordinating with field person. That’s why the idea of proposed work  is to design a system which is very cost effective. This system can be used to monitor MV/LV application also.